2047. Meningococcal burden of disease in Argentina: 10 years epidemiologic review. (15th December 2022) - Urueña, Analia; Neyro, Silvina; Efron, Adriana; Pannunzio, Maria Eugenia; Seoane, María; Gómez, Jorge; Giglio, Norberto
Abstract: Background: Reduction of Invasive meningococcal disease (IMD) burden is one of the public health main priorities in Argentina. Since 2017, MenACWY vaccination was implemented for infants (3-5 and 15 months) and adolescents (11 years). However, epidemiological studies have been scarce in recent years. Considering the changing dynamic of the disease, specially related to serogroups circulation, we decided to carry out an epidemiological review and update IMD information that contributes to assess the best prevention strategy. Methods: Retrospective 2010-2019 observational and descriptive study, based on Argentina Ministry of Health secondary data. Main outcomes included IMD incidence rates, serogroups distribution, mortality and case fatality ratios (CFR) stratified by year, age groups, (infants: 0-11 months; 1 to 4 y; 5 to 19 y; >20 to 29 y; >30 to 39 y; 40 to 49 y; 50 to 59 y; >60 y) and regions. Results: 1, 972 IMD cases were notified in the study period. Incidence reached its maximum in 2013 (0.69/100, 000) and steadily declined to 0.22-0.23/100, 000 in 2018-2019. Highest incidence rates were observed in infants (exceeding 14/100, 000 in 2012, with no adolescent's peak) and in the center of the country (reaching a value of 0.9/100, 000 in 2013). There were 167 meningococcal deaths during 2010-2019 with a downtrend since 2014. Mortality rates were 18 times higher in infants versus all other age groups. CFR for the entire period was 8.5% and increased with age (< 7% in < 20y to 26% in >60y). Serogroup identification from notified cases increased from 73% in 2010 to 91% in 2019. From all characterized strains 47% and 42% corresponded to serogroup B and W, respectively. A higher predominance of serogroup B over W was observed during the last 5 years, especially in infants and in the central region. Conclusion: The highest burden of meningococcal disease focused on children < 1yoa with a growing predominance of serogroup B. This trend highlights the importance of vaccination at very early age adding protection against serogroup B in this age group. These results will contribute to the process of evidence-based decision making. Disclosures: Analia urueña, n/a, MSD: Grant/Research Support|Received funding for investigator led studies from GSK, : Advisor/Consultant|Received funding for investigator led studies from GSK, : Grant/Research Support|Received funding for investigator led studies from GSK, : Honoraria|Sanofi: Grant/Research Support|Seqirus: Advisor/Consultant|Seqirus: Grant/Research Support|Takeda: Grant/Research Support Maria Eugenia Pannunzio, n/a, GSK Argentina: Employee María Seoane, n/a, GSK: Board Member|GSK: Stocks/Bonds Jorge Gómez, n/a, GlaxoSmithKline: Employee|GlaxoSmithKline: Stocks/Bonds Norberto Giglio, GSK: Grant/Research Support|GSK: Honoraria|Received funding for investigator led studies from GSK, : Grant/Research Support|Received funding for investigator led studies from GSK, : Honoraria|SANOFI: Grant/Research Support|SANOFI: Honoraria|Sequirus: Grant/Research Support|Sequirus: Honoraria.